Sociodemographic disparities in non‐diabetic hyperglycaemia and the transition to type 2 diabetes: evidence from the English Longitudinal Study of Ageing. Issue 9 (26th June 2020) - Chatzi, G.; Mason, T.; Chandola, T.; Whittaker, W.; Howarth, E.; Cotterill, S.; Ravindrarajah, R.; McManus, E.; Sutton, M.; Bower, P.
Abstract: Aim: To explore whether there are social inequalities in non‐diabetic hyperglycaemia (NDH) and in transitions to type 2 diabetes mellitus and NDH low‐risk status in England. Methods: Some 9143 men and women aged over 50 years were analysed from waves 2, 4, 6 and 8 (2004–2016) of the English Longitudinal Study of Ageing (ELSA). Participants were categorized as: NDH 'low‐risk' [HbA1c < 42 mmol/mol (< 6.0%)], NDH [HbA1c 42–47 mmol/mol (6.0–6.4%)] and type 2 diabetes [HbA1c > 47 mmol/mol (> 6.4%)]. Logistic regression models estimated the association between sociodemographic characteristics and NDH, and the transitions from NDH to diagnosed or undiagnosed type 2 diabetes and low‐risk status in future waves. Results: NDH was more prevalent in older participants, those reporting a disability, those living in deprived areas and in more disadvantaged social classes. Older participants with NDH were less likely to progress to undiagnosed type 2 diabetes [odds ratio (OR) 0.27, 95% confidence interval (CI) 0.08, 0.96]. NDH individuals with limiting long‐standing illness (OR 1.72, 95% CI 1.16, 2.53), who were economically inactive (OR 1.60, 95% CI 1.02, 2.51) or from disadvantaged social classes (OR 1.63, 95% CI 1.02, 2.61) were more likely to progress to type 2 diabetes. Socially disadvantaged individuals were less likely (OR 0.64, 95% CI 0.41, 0.98) to progress to NDH low‐risk status. Conclusions: There were socio‐economic differences in NDH prevalence, transition to type 2 diabetes and transition to NDH low‐risk status. Disparities in transitions included the greater likelihood of disadvantaged social groups with NDH developing type 2 diabetes and greater likelihood of advantaged social groups with NDH becoming low‐risk. These socio‐economic differences should be taken into account when targeting prevention initiatives. What's new?: Sociodemographic differences exist in the transitions from non‐diabetic hyperglycaemia to type 2 diabetes and to 'low‐risk' status in older adults. Participants with non‐diabetic hyperglycaemia who had a disability, who were economically inactive, and those living in socio‐economic disadvantage were more likely to develop type 2 diabetes in the future. Participants with non‐diabetic hyperglycaemia who were living in socio‐economic disadvantage were less likely to transition to low‐risk status in the future. Findings from this study could inform researchers in diabetes prevention programmes about the selection of participants into these programmes and the effectiveness of these programmes for disadvantaged social groups.